Pengaruh Pengetahuan Remaja tentang NAPZA dan HIV serta Pengetahuan Orang Tua tentang Program Pembangunan Keluarga terhadap Perilaku Penggunaan NAPZA pada Remaja - Nasution, Sri Lilestina; Puspitawati, Herien; Rizkillah, Risda; Puspitasari, Mardiana Dwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
The rapid increasing flow of globalization causes young people (including adolescent) experience various challenges in life. The present research proposes the role of demographic factors of young people and their family, young people’s knowledge on drug abuse and HIV, and family’s knowledge about family development program in drug using among young people. This study used secondary analysis of the 2017 Survey of Population, Family Planning and Family Development Program Performance, National Medium Term Development Plan Year 2017 (KKBPK RPJMN 2017) which was designed to produce parameter in Provincial and National levels.The unit of analysis was young people aged 15-24 years who have never been married in Indonesia. Logistic regression was applied to analyze the inferential statistics. Results indicate that the risk factors of young people which make them more likely to use drug are living in urban area, between the ages of 20-24 years, male, having low education level, having moderate drug abuse and HIV knowledge indexes. The family contexts examining the risk factors are family whose head was under 40 years of age, single-parent family, family whose head was female, family with moderate to high educational level, low level of family’s wealth, and high family development program index.